Perancangan Typeface Eksperimental Motif Aka Cino Minangkabau - Raiyanuwaldi Raiyanuwaldi; Dini Faisal (Universitas Katolik Widya Karya Malang, 2023)
Experimental typeface design of Aka cino Minangkabau motif. This design is motivated by the lack of knowledge of Minangkabau people about this carving motif. The purpose of this design is to explore the aka cino motif into the design of letters so that it can elevate local culture into contemporary works so that people, especially Minangkabau, can appreciate and preserve local culture. This design uses the 4-D model design method (Four D Models). There are four phases in this model, namely: Defining, Designing, Developing, and Deploying. The data collection method uses literature study, internet and online questionnaire distribution. The result of this design is that this typeface has represented the impression of the aka cino motif and is intended as a text headline with very good readibility and legibility.